Sams teach yourself Java in 21 days - Cadenhead, Rogers (Pearson Education, 2020)
In just 21 days, you can acquire the knowledge and skills necessary to develop applications on your computer, web servers, and mobile devices. With this complete tutorial you'll quickly master the basics and then move on to more advanced features and concepts. Completely updated for Java 11 and 12, this book teaches you about the Java language and how to use it to create applications for any computing environment. By the time you have finished the book, you'll have well-rounded knowledge of Java and the Java class libraries. No previous programming experience required. By following the 21 carefully organized lessons in this book, anyone can learn the basics of Java programming. Learn at your own pace. You can work through each chapter sequentially to make sure you thoroughly understand all the concepts and methodologies, or you can focus on specific lessons to learn the techniques that interest you most. Test your knowledge. Each chapter ends with a Workshop section filled with questions, answers, and exercises for further study. There are even certification practice questions. Completely revised, updated, and expanded to cover the latest features of Java 11 and 12 Learn to develop Java applications using NetBeans-an excellent programming platform Easy-to-understand, practical examples clearly illustrate the fundamentals of Java programming Discover how to quickly develop programs with a graphical user interface Find out about JDBC programming with the Derby database Learn how to use Inner Classes and Lambda Expressions Learn rapid application development with Apache NetBeans Create a game using Java.